Calorie restriction activates new adult born olfactory‐bulb neurones in a ghrelin‐dependent manner but acyl‐ghrelin does not enhance subventricular zone neurogenesis. (24th June 2019) - Ratcliff, Michael; Rees, Daniel; McGrady, Scott; Buntwal, Luke; Hornsby, Amanda K. E.; Bayliss, Jaqueline; Kent, Brianne A.; Bussey, Timothy; Saksida, Lisa; Beynon, Amy L.; Howell, Owain W.; Morgan, Alwena H.; et al.
Abstract: The ageing and degenerating brain show deficits in neural stem/progenitor cell (NSPC) plasticity that are accompanied by impairments in olfactory discrimination. Emerging evidence suggests that the gut hormone ghrelin plays an important role in protecting neurones, promoting synaptic plasticity and increasing hippocampal neurogenesis in the adult brain. In the present study, we investigated the role of ghrelin with respect to modulating adult subventricular zone (SVZ) NSPCs that give rise to new olfactory bulb (OB) neurones. We characterised the expression of the ghrelin receptor, growth hormone secretagogue receptor (GHSR), using an immunohistochemical approach in GHSR‐eGFP reporter mice to show that GHSR is expressed in several regions, including the OB but not in the SVZ of the lateral ventricle. These data suggest that acyl‐ghrelin does not mediate a direct effect on NSPC in the SVZ. Consistent with these findings, treatment with acyl‐ghrelin or genetic silencing of GHSR did not alter NSPC proliferation within the SVZ. Similarly, using a bromodeoxyuridine pulse‐chase approach, we show that peripheral treatment of adult rats with acyl‐ghrelin did not increase the number of new adult‐born neurones in the granule cell layer of the OB. These data demonstrate that acyl‐ghrelin does not increase adult OB neurogenesis. Finally, we investigated whether elevating ghrelin indirectly, via calorie restriction (CR), regulated the activity of new adult‐born cells in the OB. Overnight CR induced c‐Fos expression in new adult‐born OB cells but not in developmentally born cells, whereas neuronal activity was absent following re‐feeding. These effects were not present in ghrelin −/− mice, suggesting that adult‐born cells are uniquely sensitive to changes in ghrelin mediated by fasting and re‐feeding. In summary, ghrelin does not promote neurogenesis in the SVZ and OB; however, new adult‐born OB cells are activated by CR in a ghrelin‐dependent manner.